The travels of a t-shirt in the global economy : an economist examines the markets, power, and politics of world trade - Rivoli, Pietra (John Wiley & Sons, 2015)
"The keys to global business success, as taught by a T-shirt's journey, The Travels of a T-Shirt in the Global Economy is a critically-acclaimed narrative that illuminates the globalization debates and reveals the key factors to success in global business. Tracing a T-shirt's life story from a Texas cotton field to a Chinese factory and back to a U.S. storefront before arriving at the used clothing market in Africa, the book uncovers the political and economic forces at work in the global economy. Along the way, this fascinating exploration addresses a wealth of compelling questions about politics, trade, economics, ethics, and the impact of history on today's business landscape. This new printing of the second edition includes a revised preface and a new epilogue with updates through 2014 on the people, industries, and policies related to the T-shirt's life story. Using a simple, everyday T-shirt as a lens through which to explore the business, economic, moral, and political complexities of globalization in a historical context, Travels encapsulates a number of complex issues into a single identifiable object that will strike a chord with readers as they: Investigate the sources of sustained competitive advantage in different industries; Examine the global economic and political forces that explain trade patters between countries; Analyze complex moral issues related to globalization and international business; Discover the importance of cultural and human elements in international trade. This story of a simple product illuminates the many complex issues which businesspeople, policymakers, and global citizens are touched by every day."--Provided by publisher.